1970
DOI: 10.13057/nusbiosci/n060203
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of thyme plants to some antioxidants

Abstract: Abstract. Orabi SA, Talaat IM, Balbaa LK. 2014. Physiological and biochemical responses of thyme plants to some antioxidants. Nusantara Bioscience 6: 118-125. Two pot experiments were conducted to investigate the effect of tryptophan, nicotinamide and α-tocopherol (each at 50 and 100 mg/L) on plant growth, essential oil yield, and its main constituents. All treatments significantly promoted plant height, and increased fresh and dry mass (g/plant) of thyme (Thymus vulgaris L.). The treatment with 100 mg/L nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…L-tryptophan is a valuable amino acid. It may act as an osmolyte, an ion transport regulator that modulates stomatal opening and detoxifies harmful effects of heavy metals ( Orabi et al, 2014 ). Furthermore, the tryptophan pathway plays a defensive role in plants ( Hussein et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…L-tryptophan is a valuable amino acid. It may act as an osmolyte, an ion transport regulator that modulates stomatal opening and detoxifies harmful effects of heavy metals ( Orabi et al, 2014 ). Furthermore, the tryptophan pathway plays a defensive role in plants ( Hussein et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that amino acids positively affect the production and components of EOs of aromatic plants. For example, geranium, thyme, philodendron, navel orange, hyssop, and lemon plants treated with amino acids have higher EO compositions than the untreated control (Talaat, 2005;Orabi et al, 2014;Abd El-wahed et al, 2016;Aghaei et al, 2019;Khalid et al, 2019Khalid et al, , 2020. However, limited studies have been conducted on the aromatic amino acid L-phenylalanine (L-Phe), which is a key player in plant growth, development, and EO production (Pascual et al, 2016;Aghaei et al, 2019;Poorghadir, 2020).…”
Section: Introductionmentioning
confidence: 99%